A csongrádi szőlőtermelők gazdasági helyzete - Kispál, Gabriella; Liebmann, Lajos (Acta Carolus Robertus, 2011)
The study shows the economic situation of grape producers at Csongrád county, based on the use of several analytical methods. The producers have been working by adverse economic conditions for surviving for a long time, similarly producers from other wine regions and grape producing areas, beside the utilization of available good natural conditions. Their efficiency was determined, that they work in a less known region, additionally their defenselessness is larger within the chain’s relationship, because of the low market position of the wine region.
Keywords: chain; cost; yield; loss